Rancang Bangun Aplikasi E-Commerce Berbasis Android Pada Toko Suryamart Menggunakan Framework Flutter - Adilla Syafira Putri; Ade Eviyanti; Hindarto Hindarto (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Suryamart is one of the business entities of the Directorate of Business Development and Investment (DPBI) UMSIDA engaged in retail. Although Suryamart is an internal business entity, it not only serves the needs of its internal buyers - employees and lecturers, but also the needs of the general public. In carrying out its business, the author found that many general people still feel unfamiliar with Suryamart stores. In contrast, in-house shoppers are too busy to come to the store to shop in person, so they are less interested in shopping. Therefore, this research was conducted with the aim of helping internal shoppers shop effectively and efficiently, as well as improving interaction with the wider general public in the future. The author uses the waterfall software development model to minimize errors and speed up the development process because it follows a sequential development process. The result of this study is an e-commerce system consisting of applications for users and admins. This application will simplify the process of ordering buyers and management by admins.